Cascading Crises: Society in the Age of COVID-19. (November 2021) - Robinson, Laura; Schulz, Jeremy; Ball, Christopher; Chiaraluce, Cara; Dodel, Matías; Francis, Jessica; Huang, Kuo-Ting; Johnston, Elisha; Khilnani, Aneka; Kleinmann, Oliver; Kwon, K. Hazel; McClain, Noah; et al.
The tsunami of change triggered by the COVID-19 pandemic has transformed society in a series of cascading crises. Unlike disasters that are more temporarily and spatially bounded, the pandemic has continued to expand across time and space for over a year, leaving an unusually broad range of second-order and third-order harms in its wake. Globally, the unusual conditions of the pandemic—unlike other crises—have impacted almost every facet of our lives. The pandemic has deepened existing inequalities and created new vulnerabilities related to social isolation, incarceration, involuntary exclusion from the labor market, diminished economic opportunity, life-and-death risk in the workplace, and a host of emergent digital, emotional, and economic divides. In tandem, many less advantaged individuals and groups have suffered disproportionate hardship related to the pandemic in the form of fear and anxiety, exposure to misinformation, and the effects of the politicization of the crisis. Many of these phenomena will have a long tail that we are only beginning to understand. Nonetheless, the research also offers evidence of resilience on several fronts including nimble organizational response, emergent communication practices, spontaneous solidarity, and the power of hope. While we do not know what the post COVID-19 world will look like, the scholarship here tells us that the virus has not exhausted society's adaptive potential.